(untitled) (Estudos em Design, 2015)
This study aims to present an overview about the drivers’ behaviors, opinions and interaction strategies with their smartphones while driving. To reach the purposed result, an online survey was applied and was spread throughout a nationwide range. The results point out for a certain driver’s lack of care about safety matters in favor of the practicability of the smartphone use, without consider the implications of this behavior.